Milk activates the expression of cytokines via Nrf2/HO‐1 pathway in human periodontal ligament cells. Issue 6 (18th June 2015) - Choi, Sung Chul; Seo, Young Hun; Bae, Won‐Jung; Lee, Hyo‐Seol; Choi, Yeoung‐Chul; Kim, Eun‐Cheol
Abstract: Background: Milk is known as a suitable storage medium for avulsed teeth during emergency situations, but its potential toxicity on human periodontal ligament (PDL) cells has not been reported. The purpose of this study was to investigate the milk‐induced gene profiles of PDL cells in vitro by microarray analysis after storage in milk. We additionally determined whether milk activates the cytoprotective defense mechanisms via the NF‐E2‐related factor‐2 (Nrf2) and heme oxygenase‐1 (HO‐1) pathway. Material and Methods: Gene induction in cultured human PDL cells after exposure to milk for 1 and 3 h as compared with non‐treated PDL cells was analyzed by microarray analysis and subsequent RT‐PCR. Reactive oxygen species (ROS) and Western blot analysis were used to determine whether milk activates the cytoprotective defense mechanisms using the Nrf2 and HO‐1 pathway. Result: Microarray data analysis identified 868 (1 h per control) and 1782 (3 h per control) differentially expressed genes related to the duration of storage in milk. Exposure to milk for 3 and 1 h resulted in the upregulation of specific inflammatory cytokines, chemokines, and MMPs concomitant with downregulation of extracellular matrix‐related genes. Exposure to milk increased the expression of peroxiredoxin‐1, thioredoxin‐1 and heme oxygenase (HO)‐1 and stimulated the nuclear translocation of Nrf2. HO‐1 inhibitor and Nrf2 siRNA blocked the milk‐induced inflammatory response such as production of ROS, expression of cytokines, chemokines, and MMPs. Conclusion: Within the limit of this study, this study demonstrates that exposure of PDL cells to milk is associated with an upregulated expression of several pro‐inflammatory proteins and key antioxidant proteins via the activation of Nrf2/ARE pathway in PDL cells.